Philosophy of education and the curriculum - Dixon, Keith (Commonwealth and international library. Education and educational research division., 1972)
Philosophy of Education and the Curriculum is a six-chapter book that first elucidates the forms of knowledge argument and religious education. Subsequent chapters detail the mathematics, natural science, and history forms of knowledge. Moral philosophy and moral education are then explained. The last chapter provides an explanation of learning.